Hubungan Usia dan Jenis Kelamin Dengan Kejadian Penyakit Periodontal Pada Pasien Poli Gigi Puskesmas Arjasa Kabupaten Jember Tahun 2020 - Sheila Firdausi; Peni Pujiastuti; Niken Probosari (Fakultas Kedokteran Gigi Universitas Jember, 2023)
Periodontal disease according to the Ministry of Health in 2013 has a number of sufferers reaching 96.58% in Indonesia. This disease is also a disease that dominates in the Dental Polyclinic at the Arjasa Health Center, Jember Regency. Periodontal disease is a pathological process affecting the periodontium which is destructive progressively causing alveolar bone destruction and loss of the periodontal ligament. One of the factors that cause periodontal disease is age and gender. This study aims to determine the description of periodontal disease and the relationship between age and sex with periodontal disease at the Dental Polyclinic of Arjasa Public Health Center in 2020. This type of research is descriptive observational with a cross sectional approach. The research sample was the medical records of patients at the Dental Polyclinic of Arjasa Public Health Center with criteria aged 5-65 years diagnosed with periodontal disease. The data analyzed using the Chi Square test assisted by the SPSS 22.0 application. Chronic periodontitis is the most common periodontal disease suffered in the adolescent age group, namely 17-25 years and the female sex dominates. The results of the Chi Square test showed a value of (0.013,0,05) for the relationship between periodontal and gender and p value (0.001<0,05) for the relationship between periodontal and age. Females and late teens are the most common patients suffering from periodontal disease and there is a positive relationship between periodontal disease and age and gender groups.